Developing Countries and the Feldstein-Horioka Puzzle - Wacziarg, Romain (IMF Working Papers; Working Paper, 1998)
The previous literature points to a high correlation between domestic rates of investment and savings among OECD countries. Some take this as evidence of limited financial integration in the industrialized world. This paper presents new empirical results, based on an extended sample of countries. The correlation coefficient in a regression of the rate of domestic investment on the rate of domestic savings is statistically insignificant most of the time and generally smaller than 0.3 for any sample other than the OECD. This finding is robust with respect to alternative time periods, subsample and estimation methods. In particular, we control for measurement error, business cycle effects, and country-specific fixed effects.